IDENTIFICATION OF THE COMPOUNDS OF ADATHODA VASICA BY GC MS ANALYSIS AND PROBING THE MODE OF ACTION OF THE COMPOUNDS BY INSILICO STUDY - Elgal N, Sharly; R, Jasmine (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was aimed to investigate the promising compound of ethanol extracts of Adathoda vasica against respiratory isolates by GC-MS analysis and Insilico studies. Methods: The leaves of the chosen plant was extracted with ethanol, evaporated in vaccum and stored for further study. The ethanol extract was analyzed for antibacterial activity against respiratory pathogens. To determine the dosage of the extracts against target respiratory isolates, minimal inhibitory concentration has been determined by broth dilution method. The extract was screened to identify the promising compounds by GC-MS and Docking was performed using Schrodinger software to determine the effective of these compounds with target proteins against respiratory infections. Results: The ethanol extract of Adathoda vasica showed promising antibacterial activity by agar diffusion method, to determine the dosage minimal inhibitory concentration has been determined by broth dilution method (MIC=3.125mg),were highly susceptible to the extract. The ethanol extract subjected to the GC-MS analysis, based on the percentage of peak area, the 3 promising compounds were chosen for docking analysis. Insilico studies had showed effective binding with target protein 2WYP (Sialic acid binding protein) and 1X7Y(Î±-Ketoacid dehydrogenase). Conclusion: The above study concludes that plant Adathoda vasica can be used in Ayurvedic treatment and has no side effect to cure both lower and respiratory infections. Thus we can also extend our study to drug formation Keywords: Adathoda vasica, GC-MS, 2-4(but-2-yl)phenyl)propanoicacid, N,N-dimethylglycine n-Hexanedecanoic acid.